2004
DOI: 10.1308/135576104322702804
|View full text |Cite
|
Sign up to set email alerts
|

Do Referrals from Primary Dental Care for Treatment Using General Anaesthesia Comply with General Dental Council Guidelines?

Abstract: Our findings indicate a need for parents of patients referred for GA procedures to be better informed about alternatives. Improvement in the quality of referrals, perhaps with the aid of standard pro formas, would also facilitate more effective management of referred patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 4 publications
1
10
1
Order By: Relevance
“…Unlike the medical literature, 4–6 to date there have been few studies in the dental literature that deal with the quality of or attempt to improve the information contained in referral letters to other practitioners 3,7–13 . In those studies, a large number of referral letters were shown to have significant omissions 7,12 and, on average, in only 40% of referral letters was the relevant medical history documented adequately 3,11 …”
Section: Introductionmentioning
confidence: 99%
“…Unlike the medical literature, 4–6 to date there have been few studies in the dental literature that deal with the quality of or attempt to improve the information contained in referral letters to other practitioners 3,7–13 . In those studies, a large number of referral letters were shown to have significant omissions 7,12 and, on average, in only 40% of referral letters was the relevant medical history documented adequately 3,11 …”
Section: Introductionmentioning
confidence: 99%
“…Thomas et al . [7] showed that only 39·8% of referrals included a full medical history. Research in other dental specialities [3,5,6,8] reported significant omissions of information.…”
Section: Referral Document Sign Essential Information Fields Completedmentioning
confidence: 99%
“…Thomas et al . [7] found that practitioners using a form were more likely to omit their own details, only 90·4% were identifiable. Snoad et al .…”
Section: Referral Document Sign Essential Information Fields Completedmentioning
confidence: 99%
See 2 more Smart Citations